2015
DOI: 10.18632/oncotarget.3384
|View full text |Cite
|
Sign up to set email alerts
|

Powerful anti-tumor and anti-angiogenic activity of a new anti-vascular endothelial growth factor receptor 1 peptide in colorectal cancer models

Abstract: To assess the therapeutic outcome of selective block of VEGFR1, we have evaluated the activity of a new specific antagonist of VEGFR1, named iVR1 (inhibitor of VEGFR1), in syngenic and xenograft colorectal cancer models, in an artificial model of metastatization, and in laser-induced choroid neovascularization. iVR1 inhibited tumor growth and neoangiogenesis in both models of colorectal cancer, with an extent similar to that of bevacizumab, a monoclonal antibody anti-VEGF-A. It potently inhibited VEGFR1 phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…This re-enforces our data showing B20-4.1.1 inhibits VEGF120-dependent processes predominantly in the subcutaneous primary tumor for its antimetastatic effect, as well as re-enforcing a role for VEGF120 expression in conferring fibrosarcoma cells with additional advantages during the early stages of survival within the tissue of the lung that are not sensitive to anti-VEGFA therapy. As our data show, there is a high degree of redundancy in VEGFR1 ligands in mice with VEGF120-expressing tumors, particularly in plasma and lung tissue, hence targeting VEGFR1 directly may inhibit survival of disseminated cells within the lung, as found in previous studies of other tumor types (39,40). In a pilot study, we found that treatment with the VEGFR1/2 tyrosine kinase inhibitor cediranib tended to decrease survival of fs120-LS cells within the lung 48 hours after intravenous injection but this effect was not statistically significant ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 73%
“…This re-enforces our data showing B20-4.1.1 inhibits VEGF120-dependent processes predominantly in the subcutaneous primary tumor for its antimetastatic effect, as well as re-enforcing a role for VEGF120 expression in conferring fibrosarcoma cells with additional advantages during the early stages of survival within the tissue of the lung that are not sensitive to anti-VEGFA therapy. As our data show, there is a high degree of redundancy in VEGFR1 ligands in mice with VEGF120-expressing tumors, particularly in plasma and lung tissue, hence targeting VEGFR1 directly may inhibit survival of disseminated cells within the lung, as found in previous studies of other tumor types (39,40). In a pilot study, we found that treatment with the VEGFR1/2 tyrosine kinase inhibitor cediranib tended to decrease survival of fs120-LS cells within the lung 48 hours after intravenous injection but this effect was not statistically significant ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, the active role of PlGF for the recruitment and maturation of bone marrow derived progenitors involved in angiogenic and metastatic processes has been demonstrated [38, 39]. The specific inhibition of VEGFR-1 achieved with different classes of inhibitors strongly impairs tumor cell transmigration from blood compartment to target organs and metastasis establishment and growth [14, 1618]. In addition, several reports indicate that in patients the expression of PlGF, or its specific inhibition, correlate with the metastatization process associated to different tumors as larynx carcinoma [40], squamous cell carcinoma [41], thyroid carcinoma [42], ovarian cancer [43] and non-small cell lung cancer [12].…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR1 activation and PlGF markedly promotes pulmonary metastases through induction of matrix metalloproteinase-9 secretion [11, 12] and plays a crucial role in the establishment of pre-metastatic niches [13]. The functional role of PlGF/VEGFR1 in tumor metastasis establishment was further confirmed using different kind of inhibitors [14–18]. …”
Section: Introductionmentioning
confidence: 99%
“…The agent intravitreal ranibizumab blocks the phosphorylation of VEGFR1 and decreases migration capacity of TAMs in experimental colonic cancer, resulting in reduced numbers of TAMs and reduction in tumor angiogenesis. 100 Targeting Macrophage Mediated/Secreted Angiogenic Molecules…”
Section: Inhibition Of Recruitment Signals That Guide Circulatory Monmentioning
confidence: 99%